The speciﬁc features of staphylococcal skin ﬂora of sportsmen of diﬀerent specializations - V. A. Zaborova; V. G. Arzumanyan; T. A. Artemieva; L. M. Butovchenko; K. G. Gurevich; M. V. Terekhova (Сеченовский вестник)
The aim of research is to investigate the features of staphylococcal microﬂora of sportsmen of diﬀerent specializations.